Implementation of Web-Based School Academic Dashboard and Monitoring - Rozi, Fakhrur; Setiawan, Agus; Primadewi, Ardhin; Rahmawati, Catur (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Curriculum changes become the realization of ideas and the design of a learning process that emphasizes aspects of knowledge, skills and attitudes. SMAN 1 Mertoyudan implements several curricula in processing its grades which have been adjusted to Kemendikbud decisions. Currently, the scoring system is still done manually and processed by the homeroom teacher so that student guardians have difficulty monitoring children's grades during the teaching and learning process. Therefore, it is necessary to have a value monitoring system that can be accessed by student guardians online so that student guardians can find out from an early age student learning achievements. The monitoring system also provides easy access for subject teachers and homeroom teachers to manage grades, find out student learning achievements and provide assistance to students through student guardians. The system is designed to have a responsive display so that it is easily accessible from smartphones and laptops according to the web view on devices used by student guardians. This research builds a school academic monitoring system using a web-based dashboard. The results of the tests that have been carried out show that the user satisfaction level is 87.5% which can be concluded that users feel that the system created is easy to understand and understand.